Bulk Emulsions and Emulsion/ANFO Technology - A Consumer's Guide - Catherine L. VanOmmeren (International Society of Explosives Engineers, 1992)
Emulsion quality characteristics such as shelf life, handling, and sensitivity are critical to the end-user. It is therefore important that the consumer be prepared to ask his suppher specific questions. To do so, he needs to have a basic understanding of what an emulsion is and how emulsion properties can affect safety, performance, and environmental impact. The criteria to be covered include: energy, velocity, sensitivity, minimum priming, shelf life, pumpability, effect of AN quality, over-the-road handling, and formulation. The consumer will learn how each of these properties can directly affect him. The information will enable him to set minimum standards in product selection, blending, and application.